The Germanic 'Auslautgesetze' - Boutkan, Dirk, (Language and Linguistics - Book Archive pre-2000., 1995)
The overall interpretation of Old Germanic phonology and morphology has much to gain from the recent and revolutionary views that were developed in its 'mother' discipline, Indo-European linguistics. For the first time, the Germanic Auslaut problem, i.e. the interpretation of the historical development of final syllables between Proto-Indo-European and Germanic, is analyzed against the background of the modern reconstruction of Proto-Indo-European. This especially entails new interpretations of various detail problems in the field of nominal and verbal morphology. Moreover, the traditional assumption of contrasting intonations yielding different inflexional endings (e.g. circumflex *-õm > Goth ??o?? , OHG -o in the _-stem genitive plural, but acute *-_m > Goth -a , OHG -a in the _-stem accusative singular) must be replaced by a theory that is in accordance with our present-day knowledge of Proto-Indo-European as a language that most probably did not display such contrasts. It is above all the interpretation of long vowels and diphthongs in Old Germanic final syllables that has given rise to a long discussion. After the standard theory, which entered most handbooks of Old Germanic linguistics, was established, it was proven to be unlikely by new investigations. Especially Lane, in his epoch-making article (JEGP 62, 1963: 155 ff), renewed the discussion and drew interesting conclusions. Studies by Antonsen, Beck, Kortlandt, Voyles and others (sometimes dealing with other subjects than Germanic Auslaut proper) also provide materials for a new theory. With respect to this 'long vowel problem', older theories (including the standard view) and modern ideas are discussed before a new interpretation is proposed. The evidence is discussed in the form of a historical overview of the nominal and verbal morphology of the Old Germanic dialects. This part of the book can therefore also be used as a reference guide in the field of historical morphology. This approach is adopted from a recent key-study in the field of Auslaut , viz. Jones' dissertation (1979, Chapell Hill). The growing interest in the relative chronology of Lautgesetze , - which was, for example, the theme of the Leiden Fachtagung der Indogermanischen Gesellschaft of 1986 -, is met with where a chronological order of the Auslautgesetze of the separate dialects is proposed. This part of the book may serve as a stimulus for the necessary discussion of the subject. See Less